Diversity of fishes in the Alto Yuruá Basin (Ucayali, Perú) - Rengifo, Blanca (2006)
The present study compares the patterns of fish’s diversity of the Alto Yurúa Basin. The study area included three sub basins: Beu, Breu and Yurúa, all without anthropogenic impact. Fishing was carried out with trawls, 10564 individuals were collected and 185 fish’s species were identified. In regional scale, the average of the Shannon diversity index (H’) for Beu was of 2,02; for Breu 1,84 and Yuruá 1,75. The rarefaction analysis shows to Yurúa with the highest species richness (91 spp.), in comparison with Beu (87) and Breu (68). In the local scale, the diversity average (H’) was highest in lotic environments (Beu 2,04; Breu 1,90; and Yurúa 1,86), compared with respective lentics environments (Beu 1,66; Breu 1,86; and Yurúa 1,82). The highest diversity of fishes observed in lotic environments could be explained because the most of Amazonian fishes have the behavior to travel by the main channels of the rivers, while the lakes can have stress seasonal conditions (high depredation pressure and low concentrations of dissolved oxygen).